Influence of Compost, Indole-3-acetic Acid and Gibberellic Acid application on productivity of Jatropha (2020)
The problem of climate change on agricultural production and human health has brought about global need for alternative source of energy like biodiesel. In order to meet thè global demand for biodiesel, strategies to improve growth and yield of Jatropha would be of great importance. A single application of plant growth hormones (PGH) and compost was evaluated on thè growth and yield parameters of Jatropha curcas. The experiments comprises of three concentrations ( 100 mgł, 150 mgł and 200 mgł) each of indole 3 acetic acid and gibberellic acid and three rates ( 10 t\ha, 20 fvha and 40 t\ha) of compost and thè untreated soil which served as thè control. Each treatment was in four replications set up in a completely randomized design (CRD). The results revealed that gibberellic acid at 150mgł and indole-3-acetic acid at 200 mgł significantly (P<0.05) increased thè chlorophyll content, growth and dry matter yield parameters of Jatropha. However, growth and yield of Jatropha curcas were improved by thè application of compost compared to thè control, (7.25 to 9.00, 18.08 to 19.23 and 2.80 to 3.25 for number of leaves/plant, leaf area and stem girth respectively). The values were not as high when compared to plants treated with plant growth hormones. Hence, gibberellic acid or indole-3-acetic acid at 150 mgł and 200 mgł respectively could be used for rapid development of seedlings.